Nitric oxide, nitrosyl iron complexes, ferritin and frataxin: A well equipped team to preserve plant iron homeostasis - Ramírez, Leonor (2011)
Iron is a key element in plant nutrition. Iron deficiency as well as iron overload results in serious metabolic disorders that affect photosynthesis, respiration and general plant fitness with direct consequences on crop production. More than 25% of the cultivable land possesses low iron availability due to high pH (calcareous soils). Plant biologists are challenged by this concern and aimed to find new avenues to ameliorate plant responses and keep iron homeostasis under control even at wide range of iron availability in various soils. For this purpose, detailed knowledge of iron uptake, transport, storage and interactions with cellular compounds will help to construct a more complete picture of its role as essential nutrient. In this review, we summarize and describe the recent findings involving four central players involved in keeping cellular iron homeostasis in plants: nitric oxide, ferritin, frataxin and nitrosyl iron complexes. We attempt to highlight the interactions among these actors in different scenarios occurring under iron deficiency or iron overload, and discuss their counteracting and/or coordinating actions leading to the control of iron homeostasis.